Muslims of northern Mozambique and the liberation movements - Bonate, Liazzat J. K. (Social Dynamics, 2009)
Despite the fact that the liberation war occurred in northern Mozambique, where a considerable number of Muslims lived, their contribution to the independence struggle has been little studied. This paper focusses on their participation in two nationalist liberation movements, Mozambican African National Union (MANU) and Frente de Libertação de Moçambique (FRELIMO), and demonstrates that the prevailing idea in scholarship about Muslims’ aloofness from the liberation struggle is unjustified. It argues that Muslim support and participation in the liberation movements stemmed primarily from grassroots African nationalism. Like most Africans, Muslims wished to end colonialism and recover their land from the Portuguese. African Muslims of northern Mozambique were well suited to support these movements, because Islam and chieftainship were linked to each other. Chiefs were believed to be the ‘owners’ and ‘stewards’ of the land, and a majority of Muslim leaders, whether traditional chiefs (régulos, in Portuguese) or Sufi leaders (tariqa khulafa’, in Arabic), were from the chiefly clans. Most importantly, Muslims of northern Mozambique had close historical and cultural ties to Tanganyika and Zanzibar, especially through Islamic and kinship networks. The involvement of Muslims in the liberation movements of those regions, in particular in Tanganyika African National Union (TANU), inspired and encouraged the Muslims of northern Mozambique to support MANU and FRELIMO, especially since these two movements were launched in Tanganyika and Zanzibar with TANU backing and the participation of Muslim immigrants from northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Youth exclusion, violence, conflict and fragile states - Hilker, Lyndsay McLean; Fraser, Erika (Social Development Direct, 2009)
This report forms part of a portfolio of work on youth focussed on two interconnected thematic areas: youth, jobs and growth and on youth exclusion, fragile states and conflict and complements work being conducted to develop a Youth Participation Guide for DFID staff. It is intended to inform a DFID Policy Briefing and a practical Guidance Note on addressing youth exclusion and unemployment. The objectives of the study are: (i) To scope out existing evidence and analysis on the links between youth exclusion, violence, conflict and fragile states and distil this information to enable DFID (and partners) to better understand the implications for poverty elimination, state and community-building, peace-building, Disarmament, Demobilisation and Reintegration (DDR) and conflict prevention, in order to address the issues more effectively in policy and programmes; (ii) To develop a conceptual framework that renders this information manageable while still reflecting the many dimensions of this issue. The study involved a desk-based literature review and consultations with a small number of key informants from DFID, other donors, academia and youth groups. This study focuses mainly on people aged 15-24, but conceptualises “youth” as a transitional stage in life between childhood and adulthood rather than as a rigid construct based on age. It recognises the diversity of youth by gender, class, ethnicity and focuses on the multiple dimensions of exclusion that systematically disadvantage youth. It also takes a holistic approach to violence – recognising that in practice different forms of violence (e.g. political, criminal, interpersonal, extremism) may overlap and that some of the same structural and proximate factors may drive youth engagement in different forms of violence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural

Crónicas dos Motins - Granjo, Paulo (Anropocoiso - Blog de Paulo Granjo, 2008)
Mensagens correspondentes à consulta "Crónicas dos Motins".
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito

War and reconstruction in northern Mozambique - Brück, Tilman (The Economics of Peace and Security Journal, 2006)
The article discusses some of the economic effects of war in northern Mozambique. It indicates how the historical and structural features of the economy of northern Mozambique restricted post-war reconstruction and post-war poverty alleviation. These features include the dominance of only a few cash crops for export, the absence of much rural trading, poor communication infrastructure, and weak political and state institutions. The specific nature of the internal war further weakened the state through the collapse of tax revenue and export earnings and the massive growth of debt and aid, of which little reached rural northern Mozambique. The article also summarizes key aspects of the geography, climate, markets, and social institutions of northern Mozambique, which define the potential production opportunities for peasant households. Finally, the article suggests how post-war reconstruction could have been more effective in achieving faster post-war poverty alleviation in northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; conflict - civil war / conflito - guerra civil; health / saúde

Campos de batalha da cidadania no Norte de Moçambique - Temudo, Marina Padrão (Cadernos de Estudos Africanos, 2005)
Durante muitos anos, a ideia de que a guerra civil que assolou Moçambique era conduzida por um exército mercenário ao serviço de interesses externos foi considerada inquestionável, desconhecendo-se que a Renamo possuía uma base social de apoio rural e que a produção agrícola constituía uma das fontes de financiamento da guerra. Após a independência, o partido-Estado Frelimo provocou uma desestruturação social, económica, política e cultural das sociedades rurais, conduzindo um projecto de desenvolvimento e de construção da nação autoritário e centralizado, que pôs em causa direitos fundamentais de cidadania. A adesão à guerra de parte da população pode assim ser interpretada como uma tentativa de conquista desses direitos. Neste trabalho, através de dois estudos de caso contrastantes, pretende-se revelar as estratégias de reprodução social e económica que permitiram a sobrevivência das populações durante o conflito e a posterior reconstrução, mas também as múltiplas formas que a afirmação dos direitos de cidadania pode encobrir.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito; electoral geography / geografia eleitoral

Power, livelihoods and conflict: case studies in political economy analysis for humanitarian action (Humanitarian Policy Group, Overseas Development Institute, 2003)
What can political economy analysis contribute to humanitarian aid interventions? How can agencies undertake such analysis in difficult environments? This chapter introduces the findings of a study (2001-2002) of four cases: Afghanistan, the eastern Democratic Republic of the Congo (DRC), Sierra Leone and the Casamance in Senegal. Political economy analysis is best conducted alongside existing humanitarian operational activities via integration into existing analytical tools.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; power / poder

What Happens to the State in Conflict?: Political Analysis as a Tool for Planning Humanitarian Assistance - Cliffe, Lionel; Luckham, Robin (Disasters, 2000)
It is now part of received wisdom that humanitarian assistance in conflict and post-conflict situations may be ineffective or even counterproductive in the absence of an informed understanding of the broader political context in which so-called ‘complex political emergencies’ (CPEs) occur. Though recognising that specific cases have to be understood in their own terms, this article offers a framework for incorporating political analysis in policy design. It is based on a programme of research on a number of countries in Africa and Asia over the last four years. It argues that the starting-point should be an analysis of crises of authority within contemporary nation-states which convert conflict (a feature of all political systems) into violent conflict; of how such conflict may in turn generate more problems for, or even destroy, the state; of the deep-rooted political, institutional and developmental legacies of political violence; and of the difficulties that complicate the restoration of legitimate and effective systems of governance after the ‘termination’ of conflict. It then lists a series of questions which such an analysis would need to ask — less in order to provide a comprehensive check-list than to uncover underlying political processes and links. It is hoped these may be used not only to understand the political dynamics of emergencies, but also to identify what kinds of policy action should and should not be given priority by practitioners.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; governance / governação